STUDI KASUS: HANDLING STUNTING CHILDREN USING MANDALA OF HEALTH ANALYSIS - Juhairina; Maisarah; Tyas Ningrum Rahmadayanti (Fakultas Kedokteran, Universitas Palangka Raya, 2022)
Stunting is a malnutrition problem that can have short-term and long-term impacts on children who are stunted. This case study presents the solution to the problem of stunting in children with a family medicine approach using a Mandala of Health analysis. The case is a mother with a 30-month-old daughter whose height, weight, and ability lag behind her peers. Based on indicators of nutritional status, children are classified as stunted, underweight, and of dubious growth and development. The child is the 2nd child of two siblings. The causes of this situation are the wrong snacks and restrictions on children's activities by parents. Efforts are being made to provide education about toddler parenting to mothers and their closest families. Keywords: stunting, toddler, family medicine